2023
DOI: 10.3390/toxics11100844
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Cardiovascular Effects of Polycyclic Aromatic Hydrocarbons: Physical Exercise as a Protective Strategy

Gabriel A. Rojas,
Nicolás Saavedra,
Cristian Morales
et al.

Abstract: Exposure to polycyclic aromatic hydrocarbons (PAHs) present in air pollution increases cardiovascular risk. On the contrary, physical exercise is a widely used therapeutic approach to mitigate cardiovascular risk, but its efficacy in an environment of air pollution, particularly with PAHs, remains unclear. This study investigates the effects of exercise on inflammation, endothelial dysfunction, and REDOX imbalance due to PAH exposure using a mouse model. Twenty male BALB/c mice were subjected to a mixture of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Remarkably, WFS inhalation during firefighting training was associated with a decrease in microvascular function 99 while HEPA filtration to reduce indoor PM 2.5 levels improved it. 100 In a preclinical study, Rojas et al 163 noted that a single exposure to a mixture of PAHs similar to those found in WFS significantly elevated plasma concentration of IL-6, IL-1β, TNF-α, and IFN-γ in male BALB/c mice. Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction (Vcam1, Icam1, and Sele) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1.…”
Section: Spillover Of Signaling Mediators Into the Bloodstreammentioning
confidence: 82%
See 1 more Smart Citation
“…Remarkably, WFS inhalation during firefighting training was associated with a decrease in microvascular function 99 while HEPA filtration to reduce indoor PM 2.5 levels improved it. 100 In a preclinical study, Rojas et al 163 noted that a single exposure to a mixture of PAHs similar to those found in WFS significantly elevated plasma concentration of IL-6, IL-1β, TNF-α, and IFN-γ in male BALB/c mice. Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction (Vcam1, Icam1, and Sele) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1.…”
Section: Spillover Of Signaling Mediators Into the Bloodstreammentioning
confidence: 82%
“…Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction (Vcam1, Icam1, and Sele) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1. 163 Finally, Robertson et al 164 reported that a single, 4-hour-long O 3 exposure at 1 ppm concentration promoted lung inflammation and attenuated the acetylcholine-mediated vasodilatation of isolated aortas from female C57BL/6 but not CD36 −/− mice, compared with filtered air. The latter, however, was recapitulated in naïve isolated aortas from female C57BL/6 mice following treatment with serum from O 3exposed mice of both genotypes.…”
Section: Spillover Of Signaling Mediators Into the Bloodstreammentioning
confidence: 99%
“…Accordingly, Durand et al ( 155 ) reported that vigorous physical activity can reduce cardiometabolic profile parameters such as blood cholesterol-HDL ratio, triglycerides, glucose, and HDL increments in USA firefighters. Moreover, a recent study performed in male BALB/c mice observed that exercise can positively impact inflammatory cytokines and modulate gene expression related with REDOX imbalance induced by PAHs exposure ( 156 ).…”
Section: Discussionmentioning
confidence: 99%